Screening of Microwave-Assisted-Batch Extraction Parameters for Recovering Total Phenolic and Flavonoid Contents from Chromolaena odorata Leaves through Two-Level Factorial Design - Oluwaseun Ruth Alara; Abdurahman Hamid Nour; Siti Kholijah binti Abdul Mudalip (Indonesian Journal of Chemistry, 2019)
Microwave-assisted extraction (MAE) of phenolic compounds from Chromolaena odorata leaves was investigated using one-factor-at-a-time (OFAT) and two-level factorial design. The MAE parameters studied were irradiation time (A: 1–5 min); microwave power level (B: 400-800 W); extraction temperature (C: 60–80 °C); solvent/feed ratio (D: 8:1–14:1 mL/g); and ethanol concentration (E: 20–60% v/v). The optima yields of TPC and TFC were 56.13 mg GAE/g d.w. and 44.78 mg QE/g d.w., respectively were achieved from MAE of C. odorata leaf at irradiation time of 2 min, microwave power of 600 W, temperature of 60 °C, solvent:feed ratio of 10:1 mL/g, and ethanol concentration of 40% v/v through one-factor-at-time (OFAT) experimental trials. The results obtained from a two-level factorial design experiments reflected that only ethanol concentration (20–60% v/v), irradiation time (1–5 min) and microwave power level (400–800 W) had significant effects on the yields of total phenolic content (TPC) and total flavonoid content (TFC) from C. odorata leaves (p < 0.05). However, temperature and solvent/feed ratio was not significant. In addition, the interactions AB (irradiation time and microwave power) and AE (irradiation time and ethanol concentration) contributed greatly to the recovery yields.